Ningxiang pigderived Enterococcus hirae regulates the inflammatory function and enhances the protection of piglets against ETEC challenge - Zhang, Longlin; Wu, Zichen; Zhang, Zihao; Cai, Rong; Pang, Shujun; Wang, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
This study investigated the effects of Enterococcus hirae (Eh) derived from Ningxiang pigs on growth performance, diarrhea incidence, and immune responses in ETEC-challenged piglets. The results showed that compared to the CON group, ETEC infection significantly reduced the average daily gain (ADG) and average daily feed intake (ADFI), increased rectal temperature, and resulted in a diarrhea rate of up to 24%. Additionally, ETEC infection significantly increased the spleen index and the expression of inflammatory cytokines in the spleen, serum and intestine, with decreasing serum sIgA and colonic SCFAs of piglets. Compared to the ETEC group, orally Eh significantly increased ADFI in ETEC-infected piglets, reduced the diarrhea rate to 11.53%, reduced the spleen index and the expression of inflammatory cytokines in the spleen, serum and intestine, with decreasing serum sIgA and colonic SCFAs of ETEC-infected piglets. Furthermore, correlation analysis revealed that the levels of SCFAs (particularly acetate) were significantly negatively correlated with the expression levels of inflammatory cytokines in colonic and splenic tissues, suggesting that acetate may be a key metabolite in the anti-inflammatory effects of Eh. These results indicate that Eh can enhance the protection of piglets against ETEC K88 via intestine-acetate-spleen axis, thereby alleviating diarrhea and improving growth performance in piglets.